Biomonitoring of genotoxic and cytotoxic effects of gingival epithelial cells exposed to digital panoramic radiography - Anuradha Pai; Rakesh C Sharma; Raghavendra Mahadev Naik; Yadavalli Guruprasad (Wolters Kluwer Medknow Publications, 2012)
Objective: The aim of this study was to evaluate genotoxic and cytotoxic effects of low level ionizing radiation used in digital panoramic radiography on gingival epithelial cells. Materials and Methods: We included 50 healthy individuals advised for digital panoramic radiography for diagnostic purpose were included in this study. Demographic data and personal history of all subjects were recorded in a proforma before the examination. Gingival epithelial cells were obtained by gentle scraping with a modified cytobrush immediately before X-ray exposure and 10 ± 2 days later. Cytological preparations were stained according to the Feulgen/fast green method and analyzed under a light microscope. Micronuclei and degenerative nuclear alterations (pyknosis, karyolysis, karyorrhexis and condensed chromatin) were scored. Results: The frequency of formation of micronuclei was not significant with regard to age, gender and after exposure to digital panoramic radiography ( P = 0.276). However this study showed significant increase in the frequencies of nuclear alterations like karyorrhexis, pyknosis, condensed chromatin, karyolysis and indicative of cell death ( P < 0.001). Conclusion: Panoramic radiographic examination does not induce genotoxic effect like micronuclei, but it does induce cytotoxic effects leading to cell death.